جريمة الرشوة في قانون مكافحة الفساد - باي, - محمد (جامعة الوادي -University eloued, 2022)
ومن خلال هذا الموضوع أوضحنا حسن اختيار المشرع الجزائري لعبارة «المزية غير المستحقة وهي عبارة بليغة إذا ما قورنت بالعبارة التي كان يحويها قانون العقوبات في المادتين 126و 127 الملغيتان منه، وسعيا من المشرع العقابي لتطويق الرشوة من جميع الجوانب ووضع حد لها بأسهل الطرق وأيسر السيل، فقد أغنى وسائل المتابعة الجزائية بأساليب التحري الخاصة المتمثلة في التسليم المراقب والترصد الالكتروني والاختراق وضيق الخناق على من يريد الهروب بأموال الرشوة إلى خارج البلاد، بأن منع التقادم في حقهم ونص على التعاون الدولي في مجال التحريات والمتابعات والإجراءات القضائية وتجنيد الأموال وحجزها.The legislator mentioned the crime of bribery in the anti-corruption law and in the penal code. The punitive legislator himself defined the public employee in the anti-corruption law to control its meaning and distinguish it from its concept in other laws, in addition to that it is one of the pillars of the crime of bribery in the public sector, and the Algerian legislator did not fail to mention The person who commits bribery in the private sector, the person who interviews the public servant. Through this subject, we have clarified the good choice of the Algerian legislator for the term “unearned advantage,” which is an eloquent phrase when compared to the phrase contained in the Penal Code in Articles 126 and 127, both repealed from it. He enriched the means of criminal follow-up with special investigative methods represented in controlled delivery, electronic surveillance, penetration and tightening the noose on those who want to escape with bribery funds outside the country, by preventing the statute of limitations against them and stipulating international cooperation in the field of investigations, follow-ups, judicial procedures, and the recruitment and seizure of funds.
ماستر اداري
Keywords: جريمة، الرشوة ، قانون مكافحة ،الفساد; crime, bribery, anti-corruption law